(untitled) (Zien Journal of Social Sciences and Humanities, 2023)
Currently, in the Republic of Uzbekistan, the search for ways to increase the efficiency of the organization and functioning of the system of state bodies, the choice of their optimal model, the use of rational forms and methods of their impact on social processes is very relevant.